Calcifediol in the management of vitamin D deficiency-related skeletal and extraskeletal diseases: overview and clinical cases - Enrique Casado; Ester Costa; Pedro Mezquita-Raya; Rubén Andújar-Espinosa; José Luis Neyro (BioExcel Publishing Ltd, 2023)
As well as being essential for musculoskeletal health, vitamin D is involved in numerous other physiological processes. Poor vitamin D status is linked to a wide range of diseases, including cardiovascular disease, autoimmune conditions, pulmonary disorders and upper respiratory tract infections. While optimal target concentrations of serum 25-hydroxyvitamin D (25(OH)D) for health maintenance or therapeutic purposes are still the subject of debate, there is reasonable agreement that serum 25(OH)D levels <50 nmol/L (20 ng/mL) constitute vitamin D deficiency and that severe deficiency states (serum 25(OH)D levels <25-30 nmol/L ≈ 10-12 ng/ mL) should be avoided. Main strategies to maintain or improve vitamin D status are food supplementation and therapeutic use of medicinal forms of vitamin D. In this review, we examine evidence that implicates vitamin D deficiency in diverse conditions in the clinical settings of endocrinology, rheumatology, pneumology and reproductive health. Cholecalciferol (vitamin D3) is the most frequently used vitamin D supplement worldwide, though calcifediol (25-hydroxyvitamin D3) has recently become more widely available. Calcifediol is one step closer than cholecalciferol in the metabolic pathway to biologically active vitamin D. Pharmacokinetic differences between these vitamin D metabolites confer putative advantages for calcifediol in certain clinical situations. The clinical use of calcifediol is explored more closely through case studies, which illustrate its adjunctive role in the treatment of several vitamin D deficiency-related skeletal and extraskeletal diseases.